Konsep Sejarah Peradaban Islam Menurut Beberapa Ahli - M. Rifqi Baidlowi Mushlikh; Erico Abiansya; Dini Febriana Sofi; Umar Al Faruq (Journal of Religion and Social Community | E-ISSN : 3064-0326, 2024)
The concept of the history of Islamic civilization is a study that includes the development, dynamics, and contributions of Islamic civilization to the world from the time of the Prophet Muhammad to the contemporary era. According to Ibn Khaldun, Islamic civilization rests on the concept of umran or community development that is integrated with religious and cultural values. Arnold Toynbee highlighted the ability of Islamic civilization to respond to internal and external challenges through the process of cultural adaptation and assimilation. Meanwhile, Marshall Hodgson underlined the importance of Islamicate, which is the influence of Islamic culture that transcends geographical boundaries and formal religions, creating a global network of civilizations. This concept was also enriched by Seyyed Hossein Nasr who emphasized Islamic spirituality as the core of the development of science, art, and ethics in Islamic civilization. In general, the history of Islamic civilization reflects not only material and political growth, but also reflects universal values such as justice, knowledge, and humanitarian solidarity. This study shows that Islamic civilization has made a great contribution in shaping the face of world civilization, both in the aspects of science, art, and international relations.